Characterization and antibacterial application of peppermint essential oil nanoemulsions in broiler - Muhammad Jabbar; Irfan Baboo; Hamid Majeed; Zahid Farooq; Valiollah Palangi (Poultry Science, 2024)
In order to mitigate the risk of antibiotic resistance in poultry, scientists nowadays consider plant secondary metabolites to be a major organic antibacterial substitute. This study aimed to characterize and investigate the in silico, in vitro, and in vivo antibacterial effects of peppermint essential oil (PEO) in the form of a nanoemulsion (NE), termed PEONE. Menthol as a major compound of PEO has been identified by gas chromatography and mass spectroscopy (GCMS) analysis as 32.3 %, while lower droplet size, polydispersity Index (PDI), and optimum zeta potential values depicted the stability of PEONE have been observed and validated by transmission electron microscopy (TEM) micrograph image. In silico antibacterial activity was studied by molecular docking of menthol and enrofloxacin with Topoisomerase IV protein (PDB: 1s16;) of Escherichia coli K12 MG1655 and this effect was validated by in vitro and in vivo analysis. In vitro analysis, sustained release of PEONE has been observed against Escherichia coli and Staphylococcus aureus. In this study for in vivo experiments (n = 90) day-old broiler chicks were distributed into 6 dietary treatments with 5 replicates of 3 birds per replication. Dietary treatments included 1) Negative control (basal diet), 2) Positive control (basal diet + 200 µl enrofloxacin), 3) 25 µl PEONE + basal diet, 4) 50 µl PEONE + basal diet, 5) 75 µl PEONE + basal diet, and 6) 100 µl PEONE + basal diet. Analyzed data by different statistical tools confirmed that PEONE significantly affected body weight gain (BWG) with an improved feed conversion ratio (FCR) compared to the control group. A significant increase in cecal Lactobacillus count and a decrease in total coliform was observed. Positive effects on physiological parameters, visceral organs, and meat quality characteristics have been observed. In conclusion, our experiments suggest that PEONE can be used in the broiler industry as a substitute for antibiotics to minimize bacterial resistance.